Extremely stiff and lightweight auxetic metamaterial designs enabled by asymmetric strut cross-sections. (April 2022) - Seetoh, Ian P.; Leong, Brendon; Yi, Edmon Lee; Markandan, Kalaimani; Kanaujia, Pawan K.; Lai, Chang Quan
Abstract: Negative Poisson's ratio has been shown to enhance packing efficiency, impact absorption, indentation resistance, fracture resistance and acoustics attenuation in auxetic materials, making them useful for applications such as protective cases and stents. However, these benefits are usually realized at the expense of a low specific modulus and poor loading efficiencies, as auxetic structures rely on 'soft' strut bending and/ or joint rotation deformation modes to reach perceptible levels of negative Poisson's ratios. Here, a general 3D Anti-Tetrachiral (3ATC) structure was analyzed and shown that, in the limit of low relative density ( i.e lightweight structure), the trade-off between specific relative stiffness and auxeticity is linear and the maximum attainable specific relative stiffness is 1/3. If the strut cross-section is symmetric, the maximum attainable Poisson's ratio is -0.5, while that for an asymmetric cross-section depends on the specific geometry of the cross-section. Importantly, our analysis shows that the non-zero product of inertia for asymmetric cross-sections can lead to an additional twist of the joint, thereby increasing the auxeticity of the 3ATC structure. This allows the 3ATC lattice to exhibit a large specific relative stiffness for a given Poisson's ratio, which can be more than an order of magnitude higher when compared to other auxetic designs in the literature. Our analysis was validated by finite element simulations and experiments on 3ATC lattices with strut cross-sections that were square (symmetric) and L-shaped (asymmetric).